Role Of Government İn Accelerating Indian Economy’s Transition Towards A Resilient Energy System İn India - Thiruvenkadam T, Sudarsan Jayasingh, K. Sampath Kumar, N. Panchanatham (International Journal of Advanced Science and Technology, 2020)
There is a transformation going on in the Electricity Sector of India from an electricity deficit country to an electricity surplus country. Due to the concern over climate change, sustainable development and environmental pollution and other related factors, the government is also changing the energy mix from focusing only on traditional sources to investing more on the renewable energy sources such as solar power and wind energy. In order to meet the future energy needs, India cannot depend only on primary energy sources as the domestic availability of these sources are comparatively lesser than the energy requirements of the country and this will increase the import dependency which is in fact dangerous to the economy. Considering the above issues the emphasis is shifting towards renewable energy sources such as solar and wind energy.  Indian government has already started taking substantial initiatives to accelerate Indian economies’ transition towards a resilient energy system in India. That includes fiscal incentives for clean energy, price regulation and other forms of government support such as Clean Environment Cess on the use of Coal and a part of the Cess amount collected is reallocated to support initiatives for developing renewable energy. India, being a member of the G20, in 2009, is committed to “phase out the inefficient fossil fuel subsidies that encourage wasteful consumption, while providing targeted support for the poorest”.  Based on the commitment, India has already started the reforms on the subsidies on gasoline on 2010 and on diesel on 2014. Against this background, the paper discusses the role of Government, over a period of time, in accelerating Indian economy’s transition towards a resilient energy system in India. It also discusses the drivers of demand for energy in India. The study also attempts to understand the transition programs of neighbor countries and these experiences may be considered in India’s transition.  The paper gives an overall picture of Indian Energy Sector’s in the past, present and the future